2022
DOI: 10.1021/jasms.2c00146
|View full text |Cite
|
Sign up to set email alerts
|

Electron Impact Excitation of Ions from Organics on Singly Protonated Peptides with and without Post-Translational Modifications

Abstract: We report on the dissociation of singly protonated peptides by electrons using electron-activated dissociation (EAD), which comprises electron impact excitation of ions from organics (EIEIO), electronic-excitation dissociation (EED), and electron ionization dissociation (EIoD). Various singly protonated peptides were dissociated using a recently reported fast EAD device. The dissociation can be induced through two pathways: (i) vibrational dissociation similar to collision-activated dissociation (CAD, or colli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…Radical-driven dissociations, electron capture dissociation (ECD), electron transfer dissociation (ETD), or their derivative dissociation methods, have been applied extensively because ECD and ETD cleave the backbones of the glycopeptides preferentially while maintaining intact glycans at the modification sites. For glycopeptide analysis, hot ECD, which uses an electron beam with a kinetic energy ( K e ) of ∼10 eV, showed an advantage over ECD/ETD in having a higher backbone dissociation efficiency without supplemental activation by gas collision and/or an infrared laser . Methods involving a secondary activation step either during the ETD reaction (activated-ion ETD) or post ETD reaction (electron transfer/higher-energy collision dissociation (EThcD)) were also introduced to enhance backbone dissociation. The limitation of ECD/ETD is that these techniques are only applicable to multiply protonated species; however, we recently reported that high-energy electrons could localize the glycosylation site in singly protonated peptides using the EIEIO approach …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radical-driven dissociations, electron capture dissociation (ECD), electron transfer dissociation (ETD), or their derivative dissociation methods, have been applied extensively because ECD and ETD cleave the backbones of the glycopeptides preferentially while maintaining intact glycans at the modification sites. For glycopeptide analysis, hot ECD, which uses an electron beam with a kinetic energy ( K e ) of ∼10 eV, showed an advantage over ECD/ETD in having a higher backbone dissociation efficiency without supplemental activation by gas collision and/or an infrared laser . Methods involving a secondary activation step either during the ETD reaction (activated-ion ETD) or post ETD reaction (electron transfer/higher-energy collision dissociation (EThcD)) were also introduced to enhance backbone dissociation. The limitation of ECD/ETD is that these techniques are only applicable to multiply protonated species; however, we recently reported that high-energy electrons could localize the glycosylation site in singly protonated peptides using the EIEIO approach …”
Section: Introductionmentioning
confidence: 99%
“…14 Methods involving a secondary activation step either during the ETD reaction (activated-ion ETD) or post ETD reaction (electron transfer/higher-energy collision dissociation (EThcD)) were also introduced to enhance backbone dissociation. 17−20 The limitation of ECD/ETD is that these techniques are only applicable to multiply protonated species; however, we recently reported that high-energy electrons could localize the glycosylation site in singly protonated peptides 21 using the EIEIO approach. 12 Hot ECD is a promising tool to determine the glycosylation site and the backbone sequence with less glycan dissociation than AI-ETD and EThcD; however, quantitation of multiple glycosylations in a single peptide is still challenging in both Nglycosylation 22−24 and O-glycosylation.…”
Section: Introductionmentioning
confidence: 99%
“…EAD spectra may be interpreted as being of overall higher quality because the EAD mechanism combines two powerful fragmentation pathways, a reaction between small, singly charged ions and electrons followed by classic collisioninduced dissociation. 33 As a consequence, the population of precursor ions is more efficiently subjected to fragmentation than by CID alone, yielding relatively large contributions of noise and artifact ions in MS/MS spectra. Correspondingly, when the CID MS/MS spectra were analyzed, a high proportion of unfragmented precursor ions was observed.…”
Section: Currently Libgen Uses [M + H] + [M + Na] + [M + Nh 4 ] + ...mentioning
confidence: 99%
“…Improved electron activated dissociation (EAD) efficiency may be achieved by trapping the precursor ions for more extensive interactions with electrons. 49 In this study, we took advantage of a new ExD cell design on a prototype Omnitrap instrument. 50 Fig.…”
Section: Introductionmentioning
confidence: 99%